Electron transmission modification layer for perovskite solar cell, preparation method of electron transmission modification layer and perovskite solar cell

By using an electron transport modification layer composed of zinc oxide (ZnO) nanoparticles and polymers (PFN and/or PFNBr) in perovskite solar cells, the problem of insufficient photoelectric conversion efficiency and stability in perovskite solar cells is solved, and more efficient photoelectric conversion and more stable battery performance are achieved.

CN119767934APending Publication Date: 2025-04-04华能青海发电有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411972211.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing perovskite solar cells, especially those that use fullerene as the electron transport layer, have problems with insufficient photoelectric conversion efficiency and/or stability.

Method used

An electron transport modification layer is provided, including zinc oxide (ZnO) nanoparticles and polymers (PFN and/or PFNBr), prepared as a continuous dense film by solution method for modifying the fullerene electron transport layer.

Benefits of technology

It improves the photoelectric conversion efficiency and stability of perovskite solar cells, blocks the penetration and reaction between the metal electrode and the perovskite layer, and extends the device life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767934A_ABST
    Figure CN119767934A_ABST
Patent Text Reader

Abstract

The invention relates to an electron transport modification layer for a perovskite solar cell, a preparation method of the electron transport modification layer and the perovskite solar cell. Specifically, the invention relates to an electron transport modification layer for a perovskite solar cell, which is characterized in that the electron transport modification layer comprises zinc oxide (ZnO) nanoparticles and poly [9, 10-b]-1, 2, 3, 3, 3-b]-1, 3, 3-b]-1, 3, 3-b]-1, 3, 3-b] The invention relates to a poly (9, 9-di (3 '-(nitrogen, nitrogen-dimethylamino) propyl) fluorenyl-2, 7-diyl)-o-[(9, 9-di-n-octylfluorenyl-2, 7-diyl)] (PFN) and / or poly (9, 9-di (3'-(nitrogen, nitrogen-dimethylamino) propyl) fluorene]-o-[(9, 9-di-n-octylfluorenyl-7, 7 '-diethyl bromide)] (PFNBr.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to an electron transport modification layer for a perovskite solar cell, a preparation method thereof, and a perovskite solar cell. Background Art

[0002] Since the first report of solid-state perovskite solar cells, their photoelectric conversion efficiency has been rapidly improved. In addition, due to the unique optical and electrical properties and solution processability of perovskite photovoltaic materials, they have shown great potential in terms of high efficiency, lightness, flexibility and low cost. However, there is still room for improvement in the photoelectric conversion efficiency of perovskite solar cells suitable for large-scale production.

[0003] The basic structure of a perovskite solar cell generally includes a transparent electrode layer, a transport layer (including an electron transport layer and a hole transport layer), a perovskite active layer, and a back electrode layer. According to the different positions of the electron transport layer and the hole transport layer, it can be divided into a formal (nip) and a trans (pin) structure. Among them, the electron transport layer of a pin-structured perovskite solar cell is usually prepared from fullerene C60 or its derivative PCBM.

[0004] Fullerene is a hollow molecule composed entirely of carbon. It is spherical, ellipsoidal, cylindrical or tubular in shape, and contains five-membered rings, six-membered rings or even seven-membered rings. The most widely used are spherical or ellipsoidal ones, such as C60, C70, C80, etc. At present, the electron transport layer used in trans-structured perovskite photovoltaic cells and modules is usually vacuum-evaporated fullerenes, or solution-processed fullerene derivative materials. Generally speaking, the vacuum-evaporation method for preparing fullerene layers is easy to achieve large-scale and large-area preparation, but the obtained electron transport layer is relatively loose, which makes it easy for metal electrodes to penetrate into the perovskite layer through the porous fullerene layer, and the ions in the perovskite layer can also react with the metal electrode through the fullerene layer, which is not conducive to the long-term stability of the device; while the solution processing of fullerene derivative materials (such as PCBM) requires halogenated solvents, such as chlorobenzene, dichlorobenzene, etc., which are more harmful to the environment.

[0005] In view of the above problems, it is necessary to develop an electron transport modification layer for perovskite solar cells, a preparation method thereof, and a perovskite solar cell that can improve the performance of perovskite solar cells, especially perovskite solar cells using fullerene as an electron transport layer, such as photoelectric conversion efficiency and / or stability. Summary of the invention

[0006] The main purpose of the present invention is to provide an electron transport modification layer for a perovskite solar cell, a preparation method thereof and a perovskite solar cell, so as to solve the problem of insufficient photoelectric conversion efficiency and / or stability of perovskite solar cells in the prior art, especially perovskite solar cells using fullerene as an electron transport layer.

[0007] In order to achieve the above-mentioned object, the present invention provides an electron transport modification layer for perovskite solar cells on the one hand, wherein the electron transport modification layer comprises zinc oxide (ZnO) nanoparticles and poly [9,9-bis (3'- (nitrogen, nitrogen-dimethylamino) propyl) fluorenyl-2,7-diyl] - and - [(9,9-di-n-octylfluorenyl-2,7-diyl)] (PFN) and / or poly [9,9-bis (3'- (nitrogen, nitrogen-dimethylamino) propyl) fluorenyl] - and - [(9,9-di-n-octylfluorenyl-7,7'-diethyl bromide)] (PFNBr).

[0008] Furthermore, the mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer is in the range of 0.05:1 to 1:1.

[0009] Furthermore, the mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer is in the range of 0.1:1 to 0.8:1.

[0010] Furthermore, the thickness of the electron transport modification layer is in the range of 0.1-100 nm.

[0011] Furthermore, the thickness of the electron transport modification layer is in the range of 5-60 nm.

[0012] Furthermore, the thickness of the electron transport modification layer is in the range of 10-25 nm.

[0013] Another aspect of the present invention provides a perovskite solar cell, comprising:

[0014] 1) Electrode layer;

[0015] 2) Hole transport layer;

[0016] 3) Perovskite absorber layer;

[0017] 4) an electron transport layer; and

[0018] 5) The electron transport modification layer described in the above aspect.

[0019] Furthermore, the electron transport layer comprises fullerene or its derivatives.

[0020] Another aspect of the present invention provides a method for preparing the electron transport modification layer described in the above aspects, the method comprising the following steps:

[0021] 1) dissolving PFN and / or PFNBr in a solvent to obtain a solution of PFN and / or PFNBr;

[0022] 2) adding ZnO nanoparticles to the PFN and / or PFNBr solution to obtain a precursor solution;

[0023] 3) coating the precursor solution on a substrate to obtain an electron transport modification layer wet film;

[0024] 4) Annealing the electron transport modification layer wet film to obtain the electron transport modification layer.

[0025] Further, the annealing in step 4) is performed at a temperature in the range of 90-120° C., and the annealing removes the solvent remaining in the wet film of the electron transport modification layer.

[0026] By applying the technical solution of the present invention, the electron transport modification layer for perovskite solar cells of the present invention is composed of polymer (PFN and / or PFNBr) coated ZnO nanoparticles, which is a continuous and dense film, and can prevent the metal electrode from penetrating into the perovskite layer through the porous fullerene layer, and can also prevent the ions in the perovskite layer from reacting with the metal electrode through the fullerene layer, thereby improving the stability of the perovskite solar cell and the module; further, ZnO, as a wide-bandgap n-type semiconductor material, can be prepared into nanomaterials of different morphologies (such as nanoparticles, nanospheres, nanosheets, and nanorod arrays, etc.) by a solution method under low temperature conditions, and the room temperature Hall mobility of electrons in zinc oxide single crystals is as high as 200 cm 2 V -1 s -1 , has unique advantages in electron transmission and solution processing, PFN or PFNBr is also an excellent electron transport layer modification material, so ZnO and PFN and / or PFNBr combination as an electron transport layer modification layer can improve the photoelectric conversion efficiency of perovskite solar cells. In addition, the electron transport layer modification layer of the present invention can be prepared by a wet process supplemented by low temperature annealing, the preparation process is simple and easy, which is conducive to reducing costs and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0028] Figure 1 It is a schematic structural diagram of the perovskite solar cell of the present invention. DETAILED DESCRIPTION

[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0030] As described in the background art, the perovskite solar cells in the prior art, especially the perovskite solar cells using fullerene as the electron transport layer, have the problem of insufficient photoelectric conversion efficiency and / or stability. In order to solve the above technical problems, the present application provides an electron transport modification layer for perovskite solar cells, which comprises zinc oxide (ZnO) nanoparticles and poly[9,9-bis(3'-(nitrogen, nitrogen-dimethylamino)propyl)fluorenyl-2,7-diyl]-and-[(9,9-di-n-octylfluorenyl-2,7-diyl)] (PFN) and / or poly[9,9-bis(3'-(nitrogen, nitrogen-dimethylamino)propyl)fluorenyl]-and-[(9,9-di-n-octylfluorenyl-7,7'-diethyl bromide)] (PFNBr).

[0031] Among them, the molecular structure formula of PFN is as follows:

[0032]

[0033] The molecular structure of PFNBr is as follows:

[0034]

[0035] The electron transport modification layer for perovskite solar cells of the present invention is composed of polymer (PFN and / or PFNBr) coated ZnO nanoparticles, which is a continuous and dense film, and can prevent the metal electrode from penetrating into the perovskite layer through the porous fullerene layer, and can also prevent the ions in the perovskite layer from reacting with the metal electrode through the fullerene layer, thereby improving the stability of the perovskite solar cell and the component; further, ZnO, as a wide bandgap n-type semiconductor material, can be prepared into nanomaterials of different morphologies (such as nanoparticles, nanospheres, nanosheets and nanorod arrays, etc.) by a solution method under low temperature conditions, and the room temperature Hall mobility of electrons in zinc oxide single crystals is as high as 200 cm 2 V -1 s -1 PFN or PFNBr is also an excellent electron transport layer modification material. Therefore, the combination of ZnO and PFN and / or PFNBr as an electron transport layer modification layer can improve the photoelectric conversion efficiency of perovskite solar cells and can also serve as a barrier layer to increase the life of solar cells or components.

[0036] In a preferred embodiment, the electron transport modification layer comprises zinc oxide (ZnO) nanoparticles and poly [9,9-bis (3'- (nitrogen, nitrogen-dimethylamino) propyl) fluorene] - and - [(9,9-di-n-octylfluorenyl-7,7'-diethyl bromide)] (PFNBr)

[0037] In a preferred embodiment, the mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer is in the range of 0.05:1 to 1:1.

[0038] In a preferred embodiment, the mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer is in the range of 0.1:1 to 0.8:1.

[0039] The ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer can affect the photoelectric conversion efficiency of the perovskite solar cell. It is found that when the mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer is in the range of 0.05:1 to 1:1, a perovskite solar cell with good photoelectric conversion efficiency can be obtained; when the mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer is in the range of 0.1:1 to 0.8:1, it is beneficial to further improve the photoelectric conversion efficiency of the perovskite solar cell.

[0040] In a preferred embodiment, the thickness of the electron transport modification layer is in the range of 0.1-100 nm.

[0041] In a preferred embodiment, the thickness of the electron transport modification layer is in the range of 5-60 nm.

[0042] In a preferred embodiment, the thickness of the electron transport modification layer is in the range of 10-25 nm.

[0043] The thickness of the electron transport modification layer can also affect the photoelectric conversion efficiency of the perovskite solar cell. It is found that when the thickness of the electron transport modification layer is in the range of 0.1-100nm, a perovskite solar cell with good photoelectric conversion efficiency can be obtained; when the thickness of the electron transport modification layer is in the range of 5-60nm, especially in the range of 10-25nm, it is conducive to further improving the photoelectric conversion efficiency of the perovskite solar cell.

[0044] Another aspect of the present invention provides a perovskite solar cell, comprising:

[0045] 1) Electrode layer;

[0046] 2) Hole transport layer;

[0047] 3) Perovskite absorber layer;

[0048] 4) an electron transport layer; and

[0049] 5) The electron transport modification layer described in the above aspect.

[0050] In a preferred embodiment, the electron transport layer comprises fullerene or a derivative thereof.

[0051] As described above, using the electron transport modification layer of the present invention, a perovskite solar cell with improved stability and / or conversion efficiency can be obtained, especially a perovskite solar cell using fullerene as an electron transport layer.

[0052] Figure 1 Schematic diagram of the structure of the perovskite solar cell of the present invention. As an example, Figure 1 The invention shows a trans-structured perovskite solar cell, which is composed of ITO / FTO conductive glass (1), a hole transport layer (2), a perovskite absorption layer (3), an electron transport layer (4), an electron transport modification layer (5) and a back electrode layer (6).

[0053] Another aspect of the present invention provides a method for preparing the electron transport modification layer described in the above aspects, the method comprising the following steps:

[0054] 1) dissolving PFN and / or PFNBr in a solvent to obtain a solution of PFN and / or PFNBr;

[0055] 2) adding ZnO nanoparticles to the PFN and / or PFNBr solution to obtain a precursor solution;

[0056] 3) coating the precursor solution on a substrate to obtain an electron transport modification layer wet film;

[0057] 4) Annealing the electron transport modification layer wet film to obtain the electron transport modification layer.

[0058] In a preferred embodiment, the annealing in step 4) is performed at a temperature in the range of 90-120° C., and the annealing removes the solvent remaining in the wet film of the electron transport modification layer.

[0059] The detailed composition and preparation of the components of the perovskite solar cell in the embodiment of the present invention are as follows:

[0060] 1. Transparent conductive substrate: Use transparent conductive glass as the transparent electrode substrate of perovskite solar cells, for example, with a size of 30×30cm 2Commercially available FTO or ITO conductive glass. Before use, the surface of the conductive glass was ultrasonically treated with deionized water, acetone, and isopropanol for 15 minutes, then cleaned with an ultraviolet light cleaner for 10 minutes, and dried with a nitrogen stream for later use. The conductive glass in the following examples is FTO glass.

[0061] 2. Hole transport layer: On a transparent conductive glass substrate, a NiOx hole transport layer with a thickness of 10-35 nm, preferably 15-25 nm, is prepared by magnetron sputtering. In the following examples, a NiOx hole transport layer with a thickness of 22 nm is selected.

[0062] 3. Perovskite absorption layer: A perovskite absorption layer is prepared on the NiOx hole transport layer. The perovskite absorption layer is prepared by, for example, a slit coating process, and the thickness of the final perovskite absorption layer is about 250-3000nm, preferably 350-800nm, and 450nm is selected in the following examples. In the preparation of the precursor solution, the concentration of the solution (based on PbI2) is 1mol / ml, the main solvent is N,N-dimethylformamide (DMF) + N-methylpyrrolidone (NMP), and the volume ratio of the two is 7:3; the perovskite crystal structure is ABX3 (A=CH3NH3(MA), NH2CHNH2(FA), C8H9NH3(PEA) or Cs, B=Pb or Sn, X=Cl, Br, I or mixed halide), preferably Cs x FA 1-x PbI x Br 3-x In the following examples, Cs 0.15 FA 0.85 PbI 2.55 Br 0.45 .

[0063] 4. Electron transport layer: prepared on the perovskite absorption layer, the material is C60, the preparation process is vacuum thermal evaporation, the thickness is about 10-100nm, preferably 30-80nm, and 50nm is selected in the following examples.

[0064] 5. Electron transport modification layer: (1) Preparation of precursor solution: a) Prepare PFN or PFNBr solution, PFNBr is selected in the following examples, the solvent is one or more of methanol, ethanol, isopropanol, and n-butanol, preferably methanol, ethanol or isopropanol, ethanol is selected in the following examples; the solution concentration range is 0.1-5 mg / ml, preferably 0.2-3 mg / ml, 1 mg / ml is selected in the following examples; b) Weigh a certain amount of commercially available ZnO nanoparticles and disperse them into the PFN or PFNBr solution by ultrasonic dispersion, wherein the ZnO nanoparticle size is 1-50 nm, preferably 2-25 nm, 6 nm is selected in the following examples; (2) A slit coating process is used on the above-mentioned electron transport layer to prepare an electron transport modification layer wet film based on the precursor solution; (3) The obtained wet film is annealed to obtain an electron transport modification layer, the annealing temperature range is 90-120°C, preferably 100-115°C, 110°C is selected in the following examples. The wet film is solidified by low temperature annealing and residual low boiling point solvent in the wet film is removed. The solvent used in the PFN or PFNBr solution is preferably the low boiling point alcohol solution as described above, so as to facilitate the subsequent removal.

[0065] 6. Back electrode layer: Reactive plasma deposition (RPD) equipment is used to deposit tungsten-doped indium oxide (IWO) as the back electrode layer, with a thickness of 100-300 nm, preferably 120-200 nm, and 160 nm in the following embodiment.

[0066] In one embodiment, the perovskite solar cell is composed of a plurality of photovoltaic cells connected in series, and the series connection between the cells is achieved through a laser scribing process commonly used in the thin-film photovoltaic industry through four steps P1 / P2 / P3 / P4.

[0067] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0068] Comparative Example 1:

[0069] The perovskite solar cell was prepared by the following steps:

[0070] On a clean transparent conductive substrate (30×30cm 2 ) was magnetron sputtered as a hole transport layer with a thickness of 22 nm, and then annealed at 350°C for 30 minutes before use.

[0071] Cs was deposited on the annealed NiOx layer. 0.15 FA 0.85 PbI 2.55 Br 0.45Perovskite film layer and electron transport layer; the perovskite film layer is prepared by a slit coating process, and then annealed at 100°C for 30 minutes with a thickness of 450nm; the annealed substrate is moved into a vacuum chamber, and a C60 electron transport layer with a thickness of 50nm is prepared by vacuum thermal evaporation.

[0072] The IWO layer with a thickness of 160 nm was deposited as the back electrode using RPD equipment.

[0073] Embodiment 1-20:

[0074] The perovskite solar cell was prepared using the same steps as in the above comparative example 1, except that an electron transport modification layer was prepared on the electron transport layer, and then a back electrode was prepared.

[0075] Preparation of modification layer precursor solution: Prepare the modification layer precursor solution according to the above steps, wherein the mass ratio of ZnO nanoparticles to PFNBr is 0.05, 0.1, 0.5, 0.8, and 1:1 respectively. Prepare the modification layer by slit coating process, and the thickness of the modification layer is 5, 10, 25, and 60 nm respectively.

[0076] The performance parameters of the photovoltaic modules obtained in the comparative examples and embodiments under standard test conditions according to national standard 20230664-T-339 are shown in the following table.

[0077] Table 1 Photoelectric conversion efficiency of photovoltaic modules obtained in comparative examples and embodiments

[0078] Sample No. ZnO:PFNBr mass ratio Modified layer thickness Conversion efficiency (%) Comparative Example 1 - - 14.6 Example 1 0.05:1 5 15.8 Example 2 0.05:1 10 16.0 Example 3 0.05:1 25 16.8 Example 4 0.05:1 60 15.9 Example 5 0.1:1 5 16.2 Example 6 0.1:1 10 16.7 Example 7 0.1:1 25 16.3 Example 8 0.1:1 60 15.9 Example 9 0.5:1 5 16.5 Example 10 0.5:1 10 17.0 Embodiment 11 0.5:1 25 17.1 Example 12 0.5:1 60 16.0 Embodiment 13 0.8:1 5 16.4 Embodiment 14 0.8:1 10 17.3 Embodiment 15 0.8:1 25 18.2 Example 16 0.8:1 60 16.6 Embodiment 17 1:1 5 15.5 Embodiment 18 1:1 10 15.8 Embodiment 19 1:1 25 15.7 Embodiment 20 1:1 60 15.6

[0079] In Table 1, it can be seen from the comparison of Examples 1-20 and Comparative Example 1 that the perovskite solar cell using the electron transport modification layer of the present invention has an improvement in photoelectric conversion efficiency compared to the perovskite solar cell not using the electron transport modification layer. It can be seen from the comparison of Examples 1-4, 5-8, 9-12, 13-16, and 17-20 that when the thickness of the electron transport modification layer of the present invention is preferably 5-60nm, more preferably 10-25nm, it is beneficial to further improve the photoelectric conversion efficiency of the perovskite solar cell. It can also be seen from the comparison of Examples 1-4, 5-8, 9-12, 13-16, and 17-20 that when the mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer of the present invention is preferably in the range of 0.05:1 to 1:1, more preferably in the range of 0.1:1 to 0.8:1, it is beneficial to further improve the photoelectric conversion efficiency of the perovskite solar cell.

[0080] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An electron transport modification layer for a perovskite solar cell, characterized in that: The electron transport modification layer comprises zinc oxide (ZnO) nanoparticles and poly[9,9-bis(3'-(nitrogen, nitrogen-dimethylamino)propyl)fluorenyl-2,7-diyl]-and-[(9,9-di-n-octylfluorenyl-2,7-diyl)] (PFN) and / or poly[9,9-bis(3'-(nitrogen, nitrogen-dimethylamino)propyl)fluorenyl]-and-[(9,9-di-n-octylfluorenyl-7,7'-diethyl bromide)] (PFNBr).

2. The electron transport modification layer according to claim 1, characterized in that The mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer is in the range of 0.05:1 to 1:

1.

3. The electron transport modification layer according to claim 1, characterized in that The mass ratio of ZnO to PFN and / or PFNBr in the electron transport modification layer is in the range of 0.1:1 to 0.8:

1.

4. The electron transport modification layer according to claim 1, characterized in that The thickness of the electron transport modification layer is in the range of 0.1-100 nm.

5. The electron transport modification layer according to claim 1, characterized in that The thickness of the electron transport modification layer is in the range of 5-60 nm.

6. The electron transport modification layer according to claim 1, characterized in that The thickness of the electron transport modification layer is in the range of 10-25 nm.

7. A perovskite solar cell, characterized in that: The perovskite solar cell comprises: 1) Electrode layer; 2) Hole transport layer; 3) Perovskite absorber layer; 4) an electron transport layer; and 5) The electron transport modification layer according to any one of claims 1 to 6.

8. The perovskite solar cell according to claim 7, characterized in that: The electron transport layer includes fullerene or a derivative thereof.

9. A method for preparing the electron transport modification layer according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: 1) dissolving PFN and / or PFNBr in a solvent to obtain a solution of PFN and / or PFNBr; 2) adding ZnO nanoparticles to the PFN and / or PFNBr solution to obtain a precursor solution; 3) coating the precursor solution on a substrate to obtain an electron transport modification layer wet film; 4) Annealing the electron transport modification layer wet film to obtain the electron transport modification layer.

10. The method according to claim 9, characterized in that The annealing in step 4) is performed at a temperature in the range of 90-120° C., and the annealing removes the solvent remaining in the wet film of the electron transport modification layer.

Citation Information

Patent Citations

  • Perovskite-based inverted thin film solar cell and preparation method thereof

    CN105006522A

  • Non-doped hole transport material and preparation method thereof, perovskite solar cell and preparation method thereof

    CN113956220A

  • Perovskite solar cell with high electrical stability and preparation method thereof

    CN117295343A

  • Preparation method of high-efficiency wide-band-gap perovskite indoor photovoltaic device

    CN117479799A